2006
DOI: 10.1038/nri1961
|View full text |Cite
|
Sign up to set email alerts
|

Interferons, immunity and cancer immunoediting

Abstract: A clear picture of the dynamic relationship between the host immune system and cancer is emerging as the cells and molecules that participate in naturally occurring antitumour immune responses are being identified. The interferons (IFNs) - that is, the type I IFNs (IFNalpha and IFNbeta) and type II IFN (IFNgamma) - have emerged as central coordinators of tumour-immune-system interactions. Indeed, the decade-old finding that IFNgamma has a pivotal role in promoting antitumour responses became the focus for a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
1,176
3
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,381 publications
(1,223 citation statements)
references
References 107 publications
25
1,176
3
19
Order By: Relevance
“…Subsets of these cells, such as CD8 + cytotoxic T‐cells and natural killer (NK) cells, may play roles in restricting tumor development and progressive growth (de Visser et al., 2006; Dunn et al., 2006). On the other hand, a growing body of research in mouse cancer models has now implicated multiple leukocyte species as causal players in cancer initiation and progression.…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…Subsets of these cells, such as CD8 + cytotoxic T‐cells and natural killer (NK) cells, may play roles in restricting tumor development and progressive growth (de Visser et al., 2006; Dunn et al., 2006). On the other hand, a growing body of research in mouse cancer models has now implicated multiple leukocyte species as causal players in cancer initiation and progression.…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…However, within the tumor microenvironment, the balance between IL-12 and IL-23, which directly reflects Th1 and Th17 cell responses, is shifted toward IL-23 via activation of STAT3 [21,22]. Much attention has been paid to the finding that tumor stromal cells and tumor-associated macrophages, in part by producing IL-23, mainly contribute to the induction of cancer by promoting inflammation, whereas T cells suppress tumor development as part of the immunosurveillance system [23][24][25][26][27][28][29]. Recent research has provided evidence for the involvement of T cells in promoting tumor progression [28][29][30][31][32][33][34][35]; however, the precise effects of T cells and the cytokines they produce on tumorigenesis remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests that, in the case of B16 melanoma cells, IL-17 appears not to be involved in the promoting tumor growth. Resolving the mechanisms underlying these discrepancies would shed light on the regulation of anti-tumor immunity.It has been demonstrated that T cells, including abTCR 1 CD4 1 , abTCR 1 CD8 1 , and gdTCR 1 T cells, play a pivotal role in tumor immunosurveillance to eliminate tumor cells [23][24][25][26][27][28][29]. Recently, it has been shown that abTCR 1 CD4 1 and abTCR 1 CD8 1 T cells also act as tumor-promoting cells in various mouse Eur.…”
mentioning
confidence: 99%
“…9,20,21,260 Such knowledge has been instrumental for the development of a wide panel of therapeutic interventions that specifically aim at (re)establishing anticancer immunosurveillance (rather than merely causing the death of malignant cells), including peptide-based vaccination. 8,105,176,261-264 Unfortunately, it has soon become clear that the majority of immunotherapies developed so far is poorly active when employed as standalone therapeutic intervention, largely reflecting (1) natural and treatment-driven immunoediting, resulting in the selection of poorly immunogenic cancer cell populations; 115,265,266 and (2) the robust immunosuppression established by malignant cells, both locally and systemically. 267-269 In line with this notion, the vast majority of peptide-based vaccines tested in the clinic so far mediated limited, if any, therapeutic activity, despite being able to elicit tumor-targeting immune responses, at least to some degree.…”
Section: Resultsmentioning
confidence: 99%